A Study on Role and Applications of ICT in Development of Rural Areas - Rakesh Kumar, Waseem Akram Mir (International Journal of Scientific Research and Management (IJSRM), 2017)
India is an extremely diverse country with a number of disparities and divides and rural-urban divide is on eamong many such divides. About 68% of Indian population live in rural areas and is dependent mostly on a stressed agrarian economy. The rural- urban divide is as much a socio-economic and political divide as it is geographical one. Rural areas represent a traditional, unskilled or semi-skilled, poverty stricken and mostly agricultural dependent population. India being a developing country can't rely on its urban manufacturing and services sector alone and rural areas must see development. ICT can be an easy set of tools that can act as a springboard for the democratic and sustainable development of rural India. ICT can be used in e-governance i.e. regulation, capacity building and policy making thus, leading to the participation of rural people in democracy and decision making. It can be used in disaster management and early warning systems at this period of time when whole world is facing challenges from climate change. Environmentally sustainable farming solutions and information about the market price volatility can be made available to rural farmers in real time. Not only in agricultural sector but ICT can be used also for social and political development. ICT can help in financial inclusion and hence in rationalizing of food subsidies. This , currently is being promoted under JAM (Jandhan Aadhar mobile) trinity. ICT is likely to help in eliminating identity frauds ,wastage, leakage and delays in PDS system. BPL population can be informed through SMSs about the arrival of food grains. This will ensure accountability, transparency and grievance redressal. ICT can also be used as an important base for political reforms not only in rural but also in urban areas. It can bring revolution by cashless transactions thereby saving time of people and reducing opportunity costs. It can become a tool for women empowerment by promoting their products worldwide through e-commerce. ICT is surely a weapon to fight growing challenges in rural areas and hence, preparing them for an unpredictable global change.